Microbial Analysis of Greywater from Local Bathrooms and Its Health Implications in Bali Local Government Area Taraba State Nigeria - Ukwubile, Cletus Anes (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
Due to reckless ways of disposing water from the baths in Nigerians Northern towns in Bali LGA Taraba State, which was caused by poor bathrooms occasioned by poverty, many lives had been lost from deaths caused by pathogenic microbes in these recklessly exposed used waters (greywater). Objective: This research was conducted in order to determine microbial contaminants of greywaters from local bathrooms in Bali LGA of Taraba State, Nigeria, and their potential threat to the lives of people in this LGA. Methods: Greywaters from bathrooms in ten (10) communities in Bali LGA were collected and analyzed for microbial contaminants. The communities are Bali, Garba-Chede, Pamgri, Garbabi, Maihula, Suntai, Jamtari, Mayokam, Daka, and Kungana, twenty areas were sampled in each of these communities. Simple Stain was done using 5 ml methylene blue solution by adding into the specimen bottles to know if there bacteria in the samples. Acid-fast Stain was done using 5 ml Ziehl Nielsen stain each added to the labeled bottles to identify Mycobacterium sp. in the greywater samples. Stains for Cellular Features cellular features such as presence of capsule, spores and flagella were screened using India ink stain which creates a clear zone around the bacteria cell in gram negative strains, and Malachite stain which stains spores green and bacteria cell red. Differential Staining (Gram Staining Procedures) was done in which the bacteria were first stained with crystal violet and then treated with mordant in order to fix the stain inside the cell. Identification of microbial organisms down to species level was done using molecular biology technique by cleavage of microbial DNA Sequence using restriction enzymes (RE). Results: Results showed that most of the greywaters from these local bathrooms were mainly gram negative bacteria. The most disseminated species are Salmonella typhi, Vibrio cholera, Escherichia coli, Campylobacter jejuni, Staphylococcus aureus and Shigella dysenteriea, according to various restriction enzymes specific to each bacterium. The RE obtained at Collaborative Research Inc. 1365, Main Street, Massachusetts, USA; do show any abnormal cleavage pattern of the DNA sequence during electrophoresis and RE DNA digestion. Most species of the microbes were highly present in greywater from local bathrooms in Maihula, Mayokam and Garbabi. It was however not high in Bali and Suntai. Highest percentage of contamination was seen in Garbabi, Garba-Chede, Jamtari and Daka; with Campylobacter jejuni the dominant bacterium species present. Conclusion: The results showed that in areas sampled, the greywaters from local bathrooms contained mainly gram negative pathogenic bacteria with potential threat to lives, and Campylobacter jejuni, Vibrio cholera, Salmonella typhi, and E. coli were the dominant organisms.